A new species of freshwater goby (Teleostei: Gobiidae: Rhinogobius) from Xijiang, Pearl River basin, Guangxi Province, China - Chen, I-Shiung (Zootaxa, 2025)
A new species of freshwater gobiid fish of the genus Rhinogobius Gill, 1859, was collected from the hill stream of Xijang, Pearl River basin, Gangxi Province, China. Rhinogobius lingjiangensis can be well distinguished from all other congeners by the unique combination of the following features: (1) fin rays: second dorsal fin rays I/7–8 (usually I/8); anal fin rays I/6–7 (usually I/6); pectoral fin rays 16–17 (modally 16); (2) squamation: longitudinal scale series 31–32 (modally 31); perdorsal scales 5–6 (modally 6); (3) vertebral count 28; and (4) specific colouration: cheek with 7 rather wide reddish orange parallel bands in male; caudal fin base with a central blackish brown spot in male; pectoral fin base greyish with brown vertical bar in male, anterior basal 1/4 region of pectoral fin with semicircular creamy yellow region in male. A brief comparison of current species with related species will be addressed.